A Survey on Active Queue Management Techniques (International Journal of Engineering and Computer Science, 2016)
With the fast growth of current internet and service demand for multiple access has also been increased significantly. Therefore, there is huge traffic in the network which results in congestion where buffer management acts an important role. Earlier, drop tail and random drop were used as buffer management techniques with the TCP. Drop tail suffers from huge queuing delay, lockout, global synchronization problem. To overcome all these problems with earlier techniques active queue management(AQM) technique has been introduced. In active queue discipline packets are dropped or marked before buffer becomes full while in earlier technique does the same when buffer becomes full. We have various algorithms under the AQM as Random early detection(RED), Random Exponential Marking (REM), Blue and Stochastic Fair Blue (SFB), ARED, Re RED, PI controller, Robust random early detection (RRED), RED with Preferential Dropping (RED-PD) etc.